Intercultural pedagogical practices - Farías Délano, Andrea Cristina (2017)
This article describes the process of development of tools and pedagogical practices in intercultural educational contexts through a project of connection between the Early Childhood Education School of Bernardo O’Higgins University and the Guillermo Videla kindergarten in Santiago de Chile. This initiative is based on the need to support the work of the institutions in new educational realities in a systematic way and according to their own needs. As a result, a work proposal is  obtained that concerns coconstruction criteria, development of self-learning practices for the educational community and contextualization of the strategies implemented in intercultural contexts.